Implementing the Framework Curriculum at Afkaaruna Islamic Preschool, Yogyakarta, for the Habituation of Religious and Moral Values - Hesti Putrisetianingsih; Endah Tri Wahyuningsih (SALIHA: Jurnal Pendidikan & Agama Islam, 2024)
The development of a nation's civilization needs to be based on the development of moral values among citizens both as individuals and groups. The method used in this study is a qualitative method with a case study approach. The purpose of this research is to describe Afkaaruna's curriculum framework in the habituation of religious and moral values. Data collection was carried out by observation, interviews, questionnaires, and documentation. The results of the study show that: Implementation of habituation of religious values and integrated with everyday learning by using an active learning approach and learning methods such as storytelling, advice, attention and supervision, habituation, gifts, and exemplary. Habituation activities in the formation of behavior are carried out through habituation strategies which include routine activities, integrated activities, special activities and spontaneous activities. Routine activities include the flag ceremony, dhuha prayer, dirosah islamiyah, congregational dhuhur prayer, environment day, saving day, children's play, ablution, and infaq. Integrated activities include IPC (International Primary Curriculum) theme activities, namely: outdoor investigative activities, mini projects, and literacy. Special activities include Hajj rituals. While spontaneous activities include praying for friends or relatives who are sick and giving rewards.